Single Nucleotide Variants of the Human TIM-1 IgV Domain with Reduced Ability to Promote Viral Entry into Cells - Takanari Hattori; Takeshi Saito; Hiroko Miyamoto; Masahiro Kajihara; Manabu Igarashi; Ayato Takada (Viruses, 2022)
Human T-cell immunoglobulin mucin 1 (hTIM-1) is known to promote cellular entry of enveloped viruses. Previous studies suggested that the polymorphisms of hTIM-1 affected its function. Here, we analyzed single nucleotide variants (SNVs) of hTIM-1 to determine their ability to promote cellular entry of viruses using pseudotyped vesicular stomatitis Indiana virus (VSIV). We obtained hTIM-1 sequences from a public database (Ensembl genome browser) and identified 35 missense SNVs in 3 loops of the hTIM-1 immunoglobulin variable (IgV) domain, which had been reported to interact with the Ebola virus glycoprotein (GP) and phosphatidylserine (PS) in the viral envelope. HEK293T cells transiently expressing wildtype hTIM-1 or its SNV mutants were infected with VSIVs pseudotyped with filovirus or arenavirus GPs, and their infectivities were compared. Eleven of the thirty-five SNV substitutions reduced the efficiency of hTIM-1-mediated entry of pseudotyped VSIVs. These SNV substitutions were found not only around the PS-binding pocket but also in other regions of the molecule. Taken together, our findings suggest that some SNVs of the hTIM-1 IgV domain have impaired ability to interact with PS and/or viral GPs in the viral envelope, which may affect the hTIM-1 function to promote viral entry into cells.